CRITICAL ISHCEMIC ATTACK OF ARTERIAL BASIN IN TYPE 2 DIABETES MELLITUS - Matmurotov , K.J.; Sattarov , I.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Objective: to determine the nature and frequency of arterial pool damage in patients with type 2 diabetes mellitus. Research material and methods: The research method was a survey, anamnesis and study of documents from other clinics in 154 patients. The results of treatment and anamnestic data were analyzed in 154 patients for the first quarter of 2021 with purulent-necrotic foot lesions on the background of type 2 diabetes mellitus during the initial visit to the purulent department at the multidisciplinary clinic of the Tashkent Medical Academy. Results and discussion: the data obtained showed that in most cases the main type of blood flow was preserved on the hip at the level of the femoral-popliteal segment (in 73%), but there was a decrease in its speed characteristics (main-altered blood flow). When analyzing the data obtained on the timing of diabetes mellitus, it was revealed that the largest number of patients with critical ischemic attacks on the myocardium of the heart were observed in patients suffering from diabetes for 9-12 years (35.7%), brain damage in these terms was noted in 42.8% (12 patients) cases. Conclusions: in type 2 diabetes mellitus, there is a multifocal lesion of arterial pools with the development of ischemic damage to the corresponding organs and systems. In patients with diabetic gangrene of the lower extremities on the background of type 2 diabetes mellitus lasting more than 10 years, critical ischemic events from the heart were observed in 27.3% of cases, brain in 18.2 % of cases.